Toxicology evaluations of Rhaphidophora decursiva (Roxb.) Schott extract in Sprague Dawley - Arsad, Siti Suriani (2013)
Rhaphidophora decursiva (Roxb.) Schott has been widely used among Chinese community in Malaysia for treating colon cancer. The study aims to evaluate the toxic effects of the methanol extract of R. decursiva after single dose toxicity study (14-day acute toxicity study), repeated 28-day subacute toxicity and 90-day subchronic toxicity study in male Sprague Dawley rats, and also to determine the anti-proliferative activity of R. decursiva extract on colon cancer cell lines (HT-29) and normal cell lines (3T3). For toxicity study, rats were divided into 4 groups consisting of 6 rats per group for each acute, subacute and subchronic toxicity evaluations, with a total number of 72 rats. All control groups received distilled water (vehicle). For the acute toxicity, the 3 treatment groups received oral single dose of the plant extract at 700 mg/kg, 2800 mg/kg and 3500 mg/kg, respectively, and sacrificed at day 14 post administration of the plant extract. For subacute toxicity, the 3 treatment groups received daily oral dose of the plant extract at 70 mg/kg, 140 mg/kg and 210 mg/kg for 28 days. As no lethality was observed in subacute toxicity, similar doses were used for the 3 treatment groups in 90-day subchronic toxicity. The toxicity of R. decursiva extract was evaluated by the incident of lethality, cage side observations, body weight measurement, absolute and relative weight for kidneys and liver, hematological parameters such as erythrocyte count (RBC), hemoglobin (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), leucocyte count (WBC) and platelet count (Plt), then serum biochemistry parameters such as urea, creatinine (Crea), albumin (Alb), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) and histopathological analysis of kidneys and liver. No lethality or adverse toxic signs were seen during the experimental periods in all toxicity studies. Behavior, body weight, absolute and relative organ weight also showed no significant changes in all three toxicity studies. Hematological analyses revealed no statistically significant differences between groups in the studies. Serum biochemistry analyses showed no significant changes in acute and subchronic toxicity studies. Similar results were observed in subacute toxicity study. For histopathological findings, no significant changes (p>0.05) showed in liver tissue as well as kidneys tissues for all toxicity studies. Anti-proliferative activity of methanol extract of R. decursiva (Roxb.) Schott on HT-29 showed the highest sensitivity at 72 hours incubation period with IC50 value of 40 μg/mL, followed by 80 μg/mL and 260 μg/mL, respectively for 48 hours and 24 hours incubation period. Besides, the extract was found not to be cytotoxic on 3T3 (IC50 cannot be determined). In conclusion, based on clinical appearance, clinical pathological, organ pathology and histopathological results, the methanol extract of R. decursiva did not cause any toxic effects to male Sprague Dawley rats, and the oral lethal dose (LD50) of the extract is more than 3500 mg/kg, while the no-observed-adverse-effect level (NOAEL) for the extract is 210 mg/kg per day for 90 days. Besides, according to the ability of R. decursiva extracts to achieve 50% inhibition of HT-29 cell lines, the findings from this study suggest that R. decursiva extract is safe to be consumed as no toxic effect was found when tested both in in vivo and in vitro studies.